The non-linear impact of stokvel savings and banking sector development in South Africa - Lindiwe Ngcobo (AL-ARBAH: Journal of Islamic Finance and Banking, 2025)
Purpose - The study investigated the non-linear impact of stokvel savings and banking sector development in South Africa. Method - The study applied the unit root break-even test, bounds F-test or cointegration and the nonlinear autoregressive distributed lag (NARDL) model for short- and long-run asymmetric impact with economic time series data ranging from 2009Q4 to 2020Q2. Result - The results of the break-even unit root tests reveal that variables were found to be I(0) and I(1), thus confirming that variables that are I(2) were not present. The findings of NARDL bounds F-test cointegration that there is a long-run relationship between banking sector size and the selected predictors. The short- and long-run multipliers portray adjustment to a new equilibrium after positive and negative shock. Implication - The empirical results demonstrates that NARDL is not the best model to detect long-run relationship between banking sector size and its predic. Originality - This study investigated the impact of stokvel savings and banking sector size in South Africa using the non-linear autoregressive distributed lag (NARDL) bound testing approach technique. Keywords: Non-Linear Autoregressive Distributed Lag, stokvel savings, banking sector size, gross domestic product, money supply, South Africa